2000
DOI: 10.1055/s-2000-9601
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Triterpenoids from Licania heteromorpha

Abstract: Six triterpenoids having a lupane and oleane skeleton were isolated from the leaves and young branches of Licania heteromorpha Bentham var. heteromorpha and were identified as: betulinic acid 1, alphitolic acid 2, 3 beta-O-trans-p-coumaroyl alphitolic acid 3, 3 beta-O-cis-p-coumaroyl alphitolic acid 4, 3 beta-O-trans-p-coumaroyl maslinic acid 5, 3 beta-O-cis-p-coumaroyl maslinic acid 6. The antimicrobial activity of these compounds was evaluated in vitro on clinically isolated microorganisms employing a microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…20) One group has reported that betulinic acid showed antimicrobial activity against S. aureus, 21) whereas another group reported that it did not. 22) Our data support the latter result. We tested the effects of oleanolic acid and ursolic acid on E. coli, P. aeruginosa and S. marcescens, a Gram-negative bacterium.…”
Section: Mics Of Triterpenoidssupporting
confidence: 82%
“…20) One group has reported that betulinic acid showed antimicrobial activity against S. aureus, 21) whereas another group reported that it did not. 22) Our data support the latter result. We tested the effects of oleanolic acid and ursolic acid on E. coli, P. aeruginosa and S. marcescens, a Gram-negative bacterium.…”
Section: Mics Of Triterpenoidssupporting
confidence: 82%
“…Maslinic acid (2α,3β-dihydroxyolean-12-en-28-oic acid) (MA) is natural olenane-type pentacyclic triterpene found in the olive fruit and can be readily obtained from olive pomace oils [12]. Several pharmacological activities have been reported for this compound, such as anti-tumor [13,14], anti-oxidant [15,16], HIV protease inhibitor [17], antimicrobial [18], vasorelaxation [19], and anti-diabetic action mediated by inhibition of glycogen phosphorylase [20,21] and protein tyrosine phosphatase 1B [22]. In addition, it has been shown that MA displays low toxicity on non-tumoral cells [23,24] indicating that it should be safe for use in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The CHCl 3 layer was analyzed by GC using a 1-Chirasil-Val column (0.32 mm 25 m). Temperatures of the injector 15 , which was confirmed by the 13 C-and 13 C-DEPT NMR data. The 1 H-NMR spectrum of 1 ( Table 1) showed signals ascribable to a galloyl (d = 7.14, 2H, s) and a sugar moiety (two anomeric protons at d = 5.66 and 4.50).…”
Section: Extraction and Isolationmentioning
confidence: 98%